A CMOS-MEMS Piezoresistive Accelerometer with Large Proof Mass - Md Khir, Mohd Haris (2010)
This paper reports a low-cost, high-sensitivity CMOS-MEMS piezoresistive accelerometer with large proof mass. Inherent CMOS polysilicon thin film was utilized as piezoresistive material and full Wheatstone bridge was constructed through easy wiring allowed by three metal layers in CMOS thin films. The device fabrication process consists of a standard CMOS process for sensor configuration and a deep reactive ion etching (DRIE) based post-CMOS microfabrication for MEMS structure release. Bulk single-crystal silicon (SCS)substrate was included in the proof mass to increase sensor sensitivity. With a low operating power of 1.5mW, the sensitivity was measured as 0.077 mV/g prior to amplification. The sensor was characterized on a magnetic shaker based dynamic test system with a high-end commercial calibrating accelerometer as reference.